University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 8 - Section 8.4 - Integration of Rational Functions by Partial Fractions - Exercises - Page 445: 3



Work Step by Step

The form of the partial fraction decomposition is $\frac{x+4}{(x+1)^{2}}=\frac{A}{x+1}+\frac{B}{(x+1)^{2}}$ This gives $A(x+1)+B= x+4$ Equating the coefficients of x and the constant term, we get A=1, A+B=4 or B=3. Thus we can write $\frac{x+4}{(x+1)^{2}}= \frac{1}{x+1}+\frac{3}{(x+1)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.